Gaining insight on friendly jamming in a real-world IEEE 802.11 network - Berger, Daniel S.; Gringoli, Francesco; Facchi, Nicolò; Martinovic, Ivan; Schmitt, Jens (2014 Wireless Network Security, 2014)
Frequency jamming is the fiercest attack tool to disrupt wireless communication and its malicious aspects have received much attention in the literature. Yet, several recent works propose to turn the table and employ so-called friendly jamming for the benefit of a wireless network. For example, recently proposed friendly jamming applications include hiding communication channels, injection attack defense, and access control. This work investigates the practical viability of friendly jamming by applying it in a real-world network. To that end, we implemented a reactive and frame-selective jammer on a consumer grade IEEE 802.11 access point. Equipped with this, we conducted a three weeks real-world study on the jammer's performance and side-effects on legitimate traffic (the cost of jamming) in a university office environment. Our results provide detailed insights on crucial factors governing the trade-off between the effectiveness of friendly jamming (we evaluated up to 13 jammers) and its cost. In particular, we observed – what we call the power amplification phenomenon – an effect that aggravates the known hidden station problem when the number of jammers increases. However, we also find evidence that this effect can be alleviated by collaboration between jammers, which again enables effective and minimally invasive friendly jamming.